Pengaruh Pemberian Tepung Maggot Terhadap Pertumbuhan Dan Tingkat Kelulushidupan Kepiting Bakau (Scylla serrata) Di Area Ekowisata Wanasari, Tuban, Bali - I Made Kawan; I Made Takuma Wira Putra; Dewa Gede Semara Edi (GEMA AGRO, 2022)
One of the most important factor in mud crab’s (Scylla serrata) aquaculture is feed. Crab’s feeds must contain nutrients which needed by crabs, such as protein, carb, fat, vitamin, and mineral which can be found in BSF maggot flour. BSF maggot flour could be alternative feed since BSF maggot does not bring or being disease agent and maggot contain high protein, between 40% - 50%. This research investigate about BSF maggot flour percentage influence as substitute feed for mud crab’s weight growth rate and survival rate. This research was conducted from March to May 2021 in the Wanasari Fisherman Group’s Ecotourism Areas, Tuban, Bali. The method used in this research is experimental method with completely randomized design. The obtained data were analyzed by using analysis of variance (ANOVA) and continued by Least Significance Different (LSD) test. The research result showed that the use of BSF maggot flour percentage has influenced on mud crab’s weight growth, but it has no effect on the mud crab’s survival rate.